Efeito da fase em técnicas de redução de ruídos em sinais de voz baseadas na SNR a priori - Diniz, Henrique Carlos [UNESP] (2013)
The noise reduction in speech signals is important in various contexts. Among the various techniques in the literature, most of them are based in the frequency domain, with implementation through Fourier transform. The phase of the processed signal is, in these cases, the actual phase of the noisy signal. In this work, the objective is to evaluate the effects of the phase in the processing. To this end, tests were made using efficient methods of noise reduction in speech signals, based on the Spectral Subtraction and Minimizing the mean square error, implemented using the a priori signal/noise ratio. The results show that phase is important and changes the quality of the processed signal, opening studies to new techniques for noise reduction